2018
DOI: 10.1016/j.neuron.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Functional Ultrasound Imaging Reveals Brain Modules for Visuomotor Integration

Abstract: SummaryLarge numbers of brain regions are active during behaviors. A high-resolution, brain-wide activity map could identify brain regions involved in specific behaviors. We have developed functional ultrasound imaging to record whole-brain activity in behaving mice at a resolution of ∼100 μm. We detected 87 active brain regions during visual stimulation that evoked the optokinetic reflex, a visuomotor behavior that stabilizes the gaze both horizontally and vertically. Using a genetic mouse model of congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 46 publications
5
147
0
Order By: Relevance
“…Furthermore, recent studies have shown that the spatial and temporal activity recorded from WFCI and fMRI during spontaneous activity show considerable similarities 3,36 . Given these conceptual similarities, we believe there are opportunities to adapt the methods we introduced here to fMRI or other three-dimensional (3D) functional imaging modalities 37,38 , while using a 3D atlas of brain regions to aid in localization of the extracted demixed components. We hope to pursue these directions in future work.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent studies have shown that the spatial and temporal activity recorded from WFCI and fMRI during spontaneous activity show considerable similarities 3,36 . Given these conceptual similarities, we believe there are opportunities to adapt the methods we introduced here to fMRI or other three-dimensional (3D) functional imaging modalities 37,38 , while using a 3D atlas of brain regions to aid in localization of the extracted demixed components. We hope to pursue these directions in future work.…”
Section: Resultsmentioning
confidence: 99%
“…For the phantom validation experiment, a plastic micro tube (inner diameter 580 , Intramedic Inc.) was buried in a homemade agar phantom with an angle of ~ 30° (angled flow), and another plastic micro tube was aligned close to ~ 0° (transvers flow) in another homemade agar phantom. A blood solution was pumped through the tubes with a syringe pump (Harvard Apparatus) at speeds of 1,3,5,7,9,11,13,15,20,25, and 30 mm/s. SVD was performed to filter the background signal clutter by removing the first two highest singular value components.…”
Section: Phantom Experiments and Data Processingmentioning
confidence: 99%
“…Since the introduction of Power Doppler-based functional ultrasound imaging (fUS) 3 , an increasing number of studies are exploiting the truly impressive capabilities of fUS for functional brain imaging studies [4][5][6][7][8] . However, the exact relationship between the fUS signal and the underlying physiological parameters is not quantitatively established.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we developed functional ultrasound imaging to record whole-brain activity in behaving mice at a resolution of~100 lm and compared activity in healthy and FRMD7 mutant mice (Macé et al, 2018). In healthy mice, we detected 87 active brain regions during visual stimulation that evoked the optokinetic reflex.…”
Section: Computations From Retina To Cortexmentioning
confidence: 99%